Pengaruh Lingkungan Kerja dan Disiplin Kerja terhadap Kinerja Karyawan pada CV. Bintang Darmawan Silver di Denpasar Timur (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The purpose of this research is to determine the influence of the work environment and work discipline on employee performance. This research was conducted at CV. Bintang Darmawan Silver with a population of 37 employees. This research uses census techniques so that all members of the population are involved as research subjects. Primary data collection was carried out using a questionnaire. Hypothesis testing is carried out using multiple linear regression. Based on the results of the analysis, it can be concluded that: 1) the work environment has a positive and significant effect on employee performance, 2) work discipline has a positive and significant effect on employee performance, 3) the work environment and work discipline has a positive and significant effect on employee performance. In improving employee performance, the leadership of CV. Bintang Darmawan Silver is expected to increase the organizational commitment of employees so that they are able to be responsible and contribute to work optimally, distribute the number of air conditioning facilities in the form of fans and air conditioners in each section as well as carry out monitoring and intensively carry out direct supervision by being involved in the field.